Strategi Humas Pemerintah Kota Depok dalam Sosialisasi Kebijakan Car Free Day - Nur Azel Rizki Syahbani; Tria Patrianti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The air quality index in Depok City has declined over the past three years based on data from the Depok City Environmental Agency. In response to this condition, the Depok City Government implemented a Car Free Day (CFD) policy every Sunday along Jalan Margonda Raya. The CFD program aims to improve environmental quality and air conditions while encouraging public participation in healthy activities. The success of this policy depends on how effectively information regarding the rules and objectives of CFD is disseminated to the public by the Depok City Government Public Relations Office. This study aims to analyze the communication strategy employed by the Depok City Government Public Relations Office in disseminating the Car Free Day policy and to identify obstacles encountered during the dissemination process. This research uses a descriptive qualitative approach through media monitoring, direct observation, and analysis of government documents.